2013
DOI: 10.1080/07391102.2013.838518
|View full text |Cite
|
Sign up to set email alerts
|

Comparing atomistic molecular mechanics force fields for a difficult target: a case study on the Alzheimer’s amyloid β-peptide

Abstract: Macromolecular function arises from structure, and many diseases are associated with misfolding of proteins. Molecular simulation methods can augment experimental techniques to understand misfolding and aggregation pathways with atomistic resolution, but the reliability of these predictions is a function of the parameters used for the simulation. There are many biomolecular force fields available, but most are validated using stably folded structures. Here, we present the results of molecular dynamics simulati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
59
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 76 publications
(63 citation statements)
references
References 62 publications
4
59
0
Order By: Relevance
“…QM calculations were employed to derive OPLS‐AA/L force‐field parameters for the Aβ 1–42 /Cu 2+ complex, based on the fully optimized truncated copper center (Figure ). It has been shown that OPLS‐AA/L produces results for Aβ in terms of helical and β‐strand contents, calculated NMR coupling constants and chemical shifts, and radii of gyration that agree well with experimental data . Details about the parameterization procedure are presented in the supporting information (SI).…”
Section: Methodsmentioning
confidence: 55%
See 1 more Smart Citation
“…QM calculations were employed to derive OPLS‐AA/L force‐field parameters for the Aβ 1–42 /Cu 2+ complex, based on the fully optimized truncated copper center (Figure ). It has been shown that OPLS‐AA/L produces results for Aβ in terms of helical and β‐strand contents, calculated NMR coupling constants and chemical shifts, and radii of gyration that agree well with experimental data . Details about the parameterization procedure are presented in the supporting information (SI).…”
Section: Methodsmentioning
confidence: 55%
“…However, lower (∼3 % and ∼6 %) and higher (∼15 % and ∼30 %) β‐propensities have also been reported. These differences result from different force fields used, as: 1) a previous MD studies testing force fields for Aβ 1–40 also produced different β‐strand populations;, and 2) an REMD study comparing three force fields for Aβ 16–22 dimers and trimers also produced different α‐ and β‐propensities . However, the different force‐field results agree, by demonstrating that the helical propensity is the highest between residues 10 and 20, while β‐structures are preferentially adopted by C‐terminal residues.…”
Section: Discussionmentioning
confidence: 97%
“…[23][24][25]27,28,42,[44][45][46] On the other hand, the accuracy of unfolded state and IDP structural ensembles obtained using several widely-used force fields has been called into question. [25][26][27]43,[46][47][48][49][50][51][52][53] Piana et al suggested that modern force fields, including Amber ff99sb*-ildn and CHARMM 22* in particular, produce IDP and unfolded state ensembles that are on average too compact. 48 It has also been suggested that Amber force fields systematically underestimate chain dimensions of IDPs and unfolded states.…”
Section: Introductionmentioning
confidence: 99%
“…A variety of simulation methods (MD, Monte Carlo, metadynamics, replica exchange) and different levels of representation (coarse-grained, implicit solvent, all-atom with explicit water) have been used to obtain IDP ensembles. 7,[21][22][23][24][25][26][27][28][29] There are two main challenges encountered in de novo simulations.…”
Section: Introductionmentioning
confidence: 99%
“…The GROMOS 53A6 force field [35,36] was used. This forcefield has been shown to perform well in simulating proteineprotein and membrane-protein systems [37,16]. The SPC (simple point charge) water model [38] was used.…”
Section: Simulation Setupmentioning
confidence: 99%